The Effectiveness of GPS Trackers in Mapping Futsal Athletes' Movement Patterns as a Muscle Injury Prevention Strategy - Putra , Deva; Vera (Corespub, 2025)
Futsal is a high-intensity sport characterized by frequent accelerations, sudden changes in direction, and limited playing space, which places athletes especially at the amateur level at increased risk of muscle injuries. This study explores the application of GPS tracker technology to map player movement patterns and analyze their relationship with muscle injury risk in amateur futsal athletes. A total of 10 amateur male players aged 18–25 participated in this four-week quasi-experimental study. Data was collected during training and match sessions using wearable GPS devices that recorded key metrics such as distance travelled, movement speed, acceleration, and positional heatmaps. Initial analysis revealed a concentration of player movement in the central and right-wing areas of the pitch, likely due to tactical preferences and dominant-foot usage. Based on this movement mapping, a targeted intervention program was developed, including muscle strengthening, active recovery protocols, and individualized load management. Comparative analysis between Week 1 and Week 4 showed significant improvements across physical performance parameters: total distance (+11.38%), maximum speed (+7.94%), average speed (+5.10%), and high-intensity accelerations (+33.33%). Recovery time also decreased by 21.43%, suggesting enhanced adaptation and resilience. The findings emphasize the potential of GPS-based monitoring not only for performance evaluation but also as a strategic tool for injury prevention. By identifying high-load zones and tailoring training to individual profiles, coaches can implement more effective conditioning and rotation strategies. This study supports the integration of GPS technology in amateur-level training environments to improve both performance outcomes and athlete safety.